Job turnover in Irish manufacturing 1972?2006 - Lawless, Martina; Murphy, Alan P. (Economic & Social Studies, 2008)
With the recent slowdown in global economic growth, there has been considerable focus in Ireland on some high-profile job losses, particularly in the manufacturing sector. This paper places such developments into a broader context and shows that aggregate changes in the net number of jobs arise from large numbers of firms both increasing and decreasing employment simultaneously at all points in time. Even at the height of the Celtic Tiger boom when employment grew by 8 per cent, this was the result of 15 per cent growth in jobs by expanding firms offset by 7 per cent of positions being eliminated in contracting firms. One important feature of job flows is that they may contribute to productivity growth by allowing movements from low to high productivity firms. To a degree, this reflects the re-allocation of jobs from declining sectors to expanding sectors, but this is not a comprehensive explanation. A significant factor underlying job flows is the reallocation within sectors from under-performing firms to expanding firms. This study also shows that productivity growth is, on balance, positive for employment growth. On the other hand, these calculations also show how hard it is for policymakers to identify firms that will be employment and productivity growth winners.
Keywords: Employment; Manufacturing sector; Ireland; Job losses